Comparative Genomic Analysis of a Novel Strain of Taiwan Hot-Spring Cyanobacterium Thermosynechococcus sp. CL-1 - Cheng, Yen-I; Chou, Lin; Chiu, Yi-Fang; Hsueh, Hsin-Ta; Kuo, Chih-Horng; Chu, Hsiu-An (Frontiers in Microbiology, 2020)
Thermosynechococcus is a genus of thermophilic unicellular cyanobacteria that are dominant in microbial mats at about 50 to 65°C in alkaline hot springs of eastern Asia. We used PacBio SMRT Sequencing to sequence the complete genome of a novel strain of thermophilic cyanobacterium, Thermosynechococcus sp. CL-1, isolated from the Chin-Lun hot spring (pH 9.3, 62°C) in Taiwan. Genome-scale phylogenetic analysis and average nucleotide identity results suggested that CL-1 is a new species in the genus Thermosynechococcus. Comparative genome analysis revealed divergent genome structures of Thermosynechococcus strains. In addition, the distinct genetic differences between CL-1 and the other Thermosynechococcus strains are related to photosynthesis, transporters, signal transduction, the chaperone/usher system, nitric oxide protection, antibiotic resistance, prokaryotic immunity systems and other physiological processes. This study suggests that Thermosynechococcus strains have actively acquired many putative horizontally transferred genes from other bacteria that enabled them to adapt to different ecological niches and stressful conditions in hot springs.